Triangle dissections of convex polygons - Dochkova, Juliana; Mengersen, Ingrid (Utilitas Mathematica, 2005)
The maximum number Δn and the minimum number δn of incongruent triangles in a dissection of a regular convex (n+2)-gon by n-1 non-intersecting diagonals into triangles are investigated. For Δn a general formula is determined. In case of δn general bounds are presented and the exact value for special (infinite) classes of n.